A consistent path for phase determination based on transmission electron microscopy techniques and supporting simulations. (December 2018) - Konrad, Lukas; Zhao, Haishuang; Gspan, Christian; Rehr, John; Kolb, Ute; Lattemann, Martina; Kothleitner, Gerald
Highlights: Simultaneous employment of analytical TEM techniques for a less ambiguous analysis of complicated chemical phases. Comparison of FEFF9 simulated energy-differential cross-sections with hydrogenic approximations calculated with SIGMAK3 for K-edges. The role of inner-shell screening factors (s) within the hydrogenic approximation. Abstract: This work addresses aspects for the analysis of industrial relevant materials via transmission electron microscopy (TEM). The complex phase chemistry and structural diversity of these materials require several characterization techniques to be employed simultaneously; unfortunately, different characterization techniques often lack connection to yield a complete and consistent picture. This paper describes a continuous path, starting with the acquisition of 3D diffraction data – alongside classical high-resolution imaging techniques – and linking the structural characterization of hard metal industrial samples with energy-loss fine-structure simulations, quantitative electron energy-loss (EEL) and energy-dispersive X-ray (EDX) spectroscopy. Thereby, the compositional analysis of a MAX phase indicated an offset of the hydrogenic, theoretical sensitivity factors, originating from poorly-adjusted screening factors. In a next step, these results were matched against quantitative compositions and parameters obtained from X-ray spectroscopy data, carried out synchronously with EELS.